Evaluación de la absorción de dióxido de carbono (CO2) mediante la actividad fotosintética de las especies vegetales de cuatro parques (Vicente león, La Filantropía, San Francisco y La Laguna) de la ciudad de Latacunga - Caiza Quillupangui, Karen Dayana (2021)
The following research was conducted in four strategic parks of the city of Latacunga, this town is located in the center of Ecuador 89 km from Quito and 335 km from Guayaquil, is the link point between the coast, Andes and Amazon is located at 2750 meters with a population of 161 447 inhabitants. The project quantified the amount of carbon absorbed from the parks: Vicente León, San Francisco, La Filantropía and La Laguna starting with an identification of the tree species of each site to be investigated, where species such as: Aliso ( Alnus glutinosa), Alamo (Populus alba), Maple (Acer), Acacia, Cucarda (Acacia), Capiri (Sideroxylon capiri ), Japanese Carnations (Dianthus caryophyllus), Brush (Callistemon citrinus), Cholan (Tecoma stans L.), Cypress (Cupressus), Chilco (Fuchsia magellanica), Spanish Dagger(Yucca gloriosa), Eucalyptus(Eucalyptus), Fresno(Fraxinus), Laurel rosa(Nerium oleander), Nogal(Juglans regia), Morera blanco (Morus), Molle(Schinus molle), Palma fénix (Phoenix canariensis)/datilera(Phoenix dactylifera)/canaria (Phoenix canariensis), Palmito. Once this information was obtained, field data were taken, such as the number of trees per species, the diameter at breast height and the approximate density according to bibliographic reviews. Nondestructive equations were established according to (Chave et al., 2005) and (West et al., 1999) that allowed to determine the absorption of carbon dioxide through data obtained in the field, where the quantification of CO2 uptake could be achieved for each tree type at each research site in order to obtain data on the highest CO2 uptake capacity per species and per park. It was concluded that in the four parks the species with the highest CO2 absorption capacity is the phoenix palm with an estimated 113.82 ton/h per year for its physiological structure and morphological characteristics.